CORPORATE GOVERNANCE MECHANISMS AND EARNINGS MANAGEMENT DURING PRE- AND POST- CODE PERIOD OF CORPORATE GOVERNANCE IN PAKISTAN - Saleem, Faiza; Khan, Muhammad Tahir; Ilyas, Muhammad (International Journal of Psychosocial Rehabilitation, 2020)
Large number of corporate accounting scandals around the world reduces the trust and reliability of financial reports. The codes of corporate governance provide a common standard for governing a corporate business. The objective of this research study is to investigate the impact of various corporate governance mechanisms on accrual and real earnings management during pre-and post-code period of corporate governance in Pakistan. The study utilized data from non-financial firms listed on Pakistan Stock Exchange (PSX) for the period 2008-2018. The results from Fixed effect model revealed that audit committee independence, board activity are significantly negative related and CEO duality is significantly positively related with accruals earnings management in the post-code period. Whereas, institutional ownership has significant negative relationship and CEO duality have significant positive relationship with real earnings management in the post-code period of corporate governance in Pakistan. The findings have important implications for investors, regulators and legislators in order to improve governance mechanism and reducing the incidence of earnings management.